Recycled Textile and Its Impact to the Environment Cases of Imported Recycled Clothes in Indonesia - Joevi Roedyati (Eduvest - Journal of Universal Studies, 2026)
The increasing volume of imported second-hand clothes and textile waste in Indonesia has raised environmental concerns, particularly in the textile and fashion industry. The production process in this sector, which includes yarn fiber production, fabric manufacturing, and value-enhancing treatments like printing and dyeing, often contradicts the principles of environmental sustainability. This study aims to analyze the environmental impact of imported recycled clothes in Indonesia, focusing on the challenges related to product quality, accessibility, and public perception. The research also aims to provide strategic recommendations to improve sustainable textile consumption and waste management practices. This research employs a qualitative systematic review, collecting secondary data from scholarly databases like Scopus, Web of Science, and Google Scholar. Additionally, semi-structured interviews were conducted to gain insights into public perceptions of recycled fashion. The study presents novelty by focusing on recycled textiles imported into Indonesia, an area that has received limited attention compared to studies in developed countries. The research highlights the growing awareness among the younger generation regarding recycled fashion, the barriers to its adoption, and the significant environmental implications of textile waste. The results indicate that while awareness of recycled fashion is high, practical barriers such as insufficient information, price concerns, and limited accessibility hinder its adoption. The study proposes strategies for improving public awareness through targeted communication and suggests that enhancing the availability and affordability of recycled fashion products could lead to greater consumer acceptance and sustainable practices in Indonesia's fashion industry.